2022
DOI: 10.1096/fasebj.2022.36.s1.r3806
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro efficacy of a hyaluronic acid (HA) matrix ingredient containing HA, dermatan sulphate and collagen (Dermial®) versus pure HA from extraction or fermentation origin

Abstract: Introduction Hyaluronic acid (HA) is a high‐molecular‐weight polysaccharide composed of glucuronic acid and N‐acetylglucosamine. HA constitutes a major component of the extracellular matrix (ECM) of the skin. With aging, the amount of HA in skin decreases, which implies a loss of skin moisture causing wrinkles, sagging and aging of the skin. Oral supplementation with HA has been widely studied in order to provide an anti‐aging effect on the skin. There are mainly two types of HA: HA of fermentation and HA of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…More specifically, the application of this LE led to increased levels of ceramides and the number of lamellar bodies [34] in an in vitro model of skin equivalents, and when used in vivo, improvements in clinical signs were seen in a canine model of atopic dermatitis using a colony of high-IgE, experimentally sensitized atopic beagles [35]. Moreover, previous in vitro testing also supports the effects of this GAG matrix, showing enhanced proliferation and migration of fibroblasts and migration of keratinocytes, as well as increased elastin production and skin hydrating capacity [36][37][38].…”
Section: Introductionmentioning
confidence: 82%
“…More specifically, the application of this LE led to increased levels of ceramides and the number of lamellar bodies [34] in an in vitro model of skin equivalents, and when used in vivo, improvements in clinical signs were seen in a canine model of atopic dermatitis using a colony of high-IgE, experimentally sensitized atopic beagles [35]. Moreover, previous in vitro testing also supports the effects of this GAG matrix, showing enhanced proliferation and migration of fibroblasts and migration of keratinocytes, as well as increased elastin production and skin hydrating capacity [36][37][38].…”
Section: Introductionmentioning
confidence: 82%
“…For this study, the process of extraction and purification from the comb of a rooster was used to obtain not only HA, but also GAGs and collagen, thus generating an ingredient matrix composed of three biomolecules with anti-aging properties [24]. In fact, a recent study has demonstrated the superior effect of this specific ingredient as compared to pure HA from extraction or fermentation origin [37].…”
Section: Discussionmentioning
confidence: 99%
“…Glycosaminoglycans (GAGs), such as hyaluronic acid (HA) and dermatan sulfate (DS), play a role in skin disease and wound healing processes and can contribute to maintaining skin homeostasis and improve skin physiology [ 28 , 29 ]. There have been reports on the beneficial effects of the particular HA matrix ingredient Dermial ® (Bioiberica S.A.U., Palafolls, Spain) used in vitro [ 30 , 31 , 32 , 33 ]. Dermial ® contains a high concentration of HA (60–75%), DS, and collagen, and reports describe its enhancing action on proliferation and migration of both dermal fibroblasts and epidermal keratinocytes and its stimulation of the production of collagen types I and III, elastin, and GAGs, which, in turn, support the maintenance of the skin’s structure and moisture content.…”
Section: Introductionmentioning
confidence: 99%